2022
DOI: 10.1111/evo.14634
|View full text |Cite
|
Sign up to set email alerts
|

Plant phenotypic plasticity changes pollinator‐mediated selection

Abstract: Many organisms change their phenotype in response to the environment, a phenomenon called phenotypic plasticity. Although plasticity can dramatically change the phenotype of an organism, we hardly understand how this can affect biotic interactions and the resulting phenotypic selection. Here, we use fast cycling Brassica rapa plants in an experiment in the greenhouse to study the link between plasticity and selection. We detected strong plasticity in morphology, nectar, and floral scent in response to differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 78 publications
2
26
0
Order By: Relevance
“…Overall, this raises the possibility that variation of relative scent composition in DAO ( Figure 1F ) could be subject to different selection pressures by fly pollinators (see also Chartier et al., 2013 ; Szenteczki et al., 2021 ; Gfrerer et al., 2022 ). However, we caution that other than pollinator-related factors can maintain variation in floral scent and affect the reproductive success of plant species, such as resource limitation ( Albre et al., 2003 ), herbivory ( Knauer and Schiestl, 2017 ; Ramos and Schiestl, 2019 ; Rusman et al., 2019 ), and potential seasonal variation in floral scent ( Dorey and Schiestl, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this raises the possibility that variation of relative scent composition in DAO ( Figure 1F ) could be subject to different selection pressures by fly pollinators (see also Chartier et al., 2013 ; Szenteczki et al., 2021 ; Gfrerer et al., 2022 ). However, we caution that other than pollinator-related factors can maintain variation in floral scent and affect the reproductive success of plant species, such as resource limitation ( Albre et al., 2003 ), herbivory ( Knauer and Schiestl, 2017 ; Ramos and Schiestl, 2019 ; Rusman et al., 2019 ), and potential seasonal variation in floral scent ( Dorey and Schiestl, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Herbivory by aphids on this plant species also affected floral scent emissions. 177 The amounts of 88 , 111 , methyl benzoate ( 100 ) and methyl salicylate ( 125 ) were decreased, whereas 1-butene-4-isothiocyanate ( 137 ) and ( Z )-3-hexenyl acetate ( 110 ) increased. For B. rapa , it was also shown that herbivory not only has direct effects on floral scent emissions, but also influences the evolution of floral scents.…”
Section: Effects Of Abiotic and Biotic Factors On Floral Scent Emissionsmentioning
confidence: 99%
“…[276][277][278][279][280][281][282] Here a few examples for studies that successfully identied compounds that elicit behavioral responses in mosquitoes are given. Otienoburu et al 283 analysed oral scents in the common milkweed Asclepias syriaca, which is visited by the northern house mosquito, Culex pipiens, and demonstrated that a blend of benzaldehyde ( 88), phenylacetaldehyde (83), and (E)-2-nonenal (177) is key in the attraction of the mosquitoes to the owers. Similarly, acetophenone (135) from sweet alyssum (Lobularia maritima) owers successfully attracted the yellow fever mosquito, Aedes aegypti.…”
Section: Fliesmentioning
confidence: 99%
See 2 more Smart Citations